Acute pyogenic meningoencephalitis due to Streptococcus pneumoniae serotype 11A in a previously healthy child: a case report - Dey, Smita; J., Jayakaviyah; P., Krithika A. (International Journal of Research in Medical Sciences, 2025)
Streptococcus pneumoniae is a leading cause of bacterial meningitis in children despite the widespread use of pneumococcal conjugate vaccines (PCVs). We report a case of acute pyogenic meningoencephalitis in a 6-year-old previously healthy male child who presented with high-grade fever, vomiting, and neck stiffness. Cerebrospinal fluid (CSF) analysis revealed neutrophilic pleocytosis, elevated proteins, low glucose, and Gram-positive diplococci. CSF culture confirmed Streptococcus pneumoniae, later identified as serotype 11A - a non-vaccine serotype not covered by PCV10, PCV13, or PCV14. The child responded to intravenous ceftriaxone, vancomycin, dexamethasone, and supportive therapy. This case highlights the clinical features and management of pneumococcal meningoencephalitis due to serotype 11A, underlining the growing burden of non-vaccine serotypes and the importance of extended-serotype vaccines.